Fruits and Vegetables and Lung Cancer Risk in Never Smokers. A Multicentric and Pooled Case-Control Study. (7th February 2022) - García-Lavandeira, José Antonio; Ruano-Ravina, Alberto; Torres-Durán, María; Parente-Lamelas, Isaura; Provencio, Mariano; Varela-Lema, Leonor; Fernández-Villar, Alberto; Piñeiro, María; Barros-Dios, Juan Miguel; Pérez-Ríos, Mónica
Abstract: Background: The etiology of lung cancer in never smokers is partly unknown. We aimed to assess the effect of fruits and vegetables consumption on lung cancer risk in never smokers. Methods: We pooled five multicenter case-control studies performed in Northwestern Spain. Cases and controls were all never smokers. All lung cancer cases had anatomopathological confirmed diagnoses. We performed a multivariate logistic regression to analyze the effect of different types of fruits and vegetables consumption on lung cancer risk. Results: A total of 438 cases and 781 controls were included. We observed that a consumption from one to six times per week shows a negative association with lung cancer risk for: kiwis (OR 0.67; 95%CI 0.46-0.95), oranges (OR 0.55; 95%CI 0.37-0.80), turnip tops (OR 0.48; 95%CI 0.34-0.66), "berza gallega" (OR 0.70; 95%CI 0.51-0.97) and broccoli (OR 0.55; 95%CI 0.35-0.83) compared to less than once a week consumption. On the other hand, we found an increased risk for lung cancer with a daily consumption of tomatoes, carrots and potatoes. Conclusions: Oranges, kiwis, turnip tops, berza gallega and broccoli may play a protective role on lung cancer development in never smokers while tomatoes, carrots and potatoes might have some association with this disease.